Identification and Characterisation of Salmonella spp. Isolated from Stool Samples of a Food Poisoning Outbreak in Chite, Mizoram, India due to Consumption of Bekang-Um (Fermented Soybean) - Belinda L Vangchhia; Sairengpuii Hnamte; Nirensingh Koch; Lalthlengliani; Tapan Kumar Dutta (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Traditional fermented soybean (“bekang-um”) is widely consumed by the indigenous Mizo tribe in Mizoram and plays a significant part of the local staple food. They are commonly prepared with herbs like culantro and often with just locally dried chilli flakes, implying it is mostly consumed raw without further cooking. Though it plays a staple part of the diet because of its unique taste, awareness on proper and regulated hygienic conditions during its preparation and fermentation processes is quite negligent. The fermentation process often warrants for the growth of not only commensal lactic acid fermenter bacteria like Acinetobacter spp., Lactobacillus spp., but also provides ample growth conditions for harmful bacteria like Salmonella spp., Clostridium spp., Intestinal Pathogenic E.Coli (IPEC) and Bacillus cereus. Aim: Phenotypic and molecular characterisation of Salmonella spp. isolated from the fermented food product bekang-um. Materials and Methods: The cross-sectional study was conducted within three months (October to December, 2020) in Multidisciplinary Research Unit (MRU), Zoram Medical College in collaboration with the Department of Veterinary Microbiology, CVSc and AH, Central Agricultural University, Selesih, Mizoram. A total of 18 stool samples were collected from patients (living in Chite, a small locality in Aizawl) who were still exhibiting symptoms of food poisoning (diarrhoea, vomiting and nausea) after consumption of fermented soybean all bought from their local neighbourhood fermenter and seller of the food item. The data was tabulated and statistically analysed using Microsoft Excel and sensitivity/resistance patterns were expressed in percentages. Results: Salmonella spp. was isolated from 17 out of 18 stool samples collected. Out of 17 samples, 15 exhibited Multi-Drug Resistance (MDR) phenotypically to clinically relevant and widely used antibiotics like cefotaxime, ceftriaxone, ciprofloxacin, amoxicillin-clavulanic acid. Alarmingly, resistance genes like blaCTX-M1 (70.6%), blaCTX-M2 (35.3%), blaSHV (70.6%), blaTEM (52.9%), blaNDM (5.8%), blaAmpC (100%), blaKPC (29.4%), blaVIM (23.5%), blaIMP (11.8%) were commonly detected. Moreover, Salmonella virulence determinants like invA (41.2%), stn (41.2%), and biofilm-associated virulence genes like csgA (11.8%), csgD (70.6%) and adrA (5.9%) were also identified. Conclusion: The identification and characterisation of Salmonella spp. isolated from a widely consumed food product “bekang-um” (fermented soybean) with co-occurring crucial virulence, biofilm-producing and resistance gene determinants is quite alarming. The findings suggest the urgent need of implementing food safety conditions and proper preparation standards of the exotic food item, and the seriousness of the potential threat it can cause in cases of unhygienic fermentation processes.